Attualità psicopatologica del perturbante - Riccardo Galiani (Marp Edizioni, 2019)
The paper moves analysing the syntagma "inquietante estraneità" (uncanny, disturbing strangeness, translation of "inquietanteétrangeté", "Unheimliche" French's translation) and some others connected lexical forms. The aim is to investigate some relationship's dimensions between ego's functions and what can appears as "stranger" to the ego himself. As a dream and the Fédida's research seem to suggest, the formlessness' area is an important factor of the stranger's meaning for the ego.